2014
DOI: 10.1038/pcan.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PSF1 as a prognostic biomarker for prostate cancer

Abstract: PSF1 is expressed in high-grade prostate cancer and may be a useful biomarker to identify patients with a poor prognosis at the time of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…GINS1 (also known as PSF1 ) is a subunit of the GINS (Go, lchi, Nii, San) complex which drives the unwinding of DNA in front of the replication fork [ 41 ]. Many studies have shown that GINS1 is up-regulated in several cancer types including lung, colon, prostate, colorectal and breast cancers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. It is reported that GINS1 is expressed widely in early embryogenesis in mice, stem and progenitor cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…GINS1 (also known as PSF1 ) is a subunit of the GINS (Go, lchi, Nii, San) complex which drives the unwinding of DNA in front of the replication fork [ 41 ]. Many studies have shown that GINS1 is up-regulated in several cancer types including lung, colon, prostate, colorectal and breast cancers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. It is reported that GINS1 is expressed widely in early embryogenesis in mice, stem and progenitor cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression correlated with poor overall survival and progression-free survival in prostate cancer patients. 18 However, the impact of GINS1 in the pathogenesis of CRC is not well defined. Herein, we performed cell experiments in vivo and in vitro to determine GINS1 expression with the progression of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Psf1 expression was found to be an independent prognostic marker for poor survival in NSCLC patients treated with surgery after preoperative chemotherapy or chemoradiotherapy (Kanzaki et al, 2016 ). Increased expression of Psf1 was associated with aggressiveness of hepatocellular carcinoma and prostate cancer (Tahara et al, 2015 ; Zhou et al, 2015 ). Overexpression of Psf2 was detected in intrahepatic cholangiocarcinoma, and tumorigenesis was promoted by elevated expression of Psf2 in early-stage cervical cancer (Obama et al, 2005 ; Ouyang et al, 2017 ).…”
Section: The Cmg As a Potential Target For Cancer Therapymentioning
confidence: 99%